Groove Planting System (GPS) Analysis of The Growth of Teak (Tectona grandis) in Ex-Lime Stone mining land - Nurtjahyani, Supiana Dian; Oktafitria, Dwi; Wulan, Sri; Arifin, Ahmad Zainal; Purnomo, Eko (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 3 (2022): ATBES, 2022)
The groove planting system (GPS) is one of the modifications in the plant planting system on ex-limestone mining land. The method used in the implementation of the GPS is to create a basin in the form of an elongated groove on the ex-limestone mining land that has not been reclaimed. Tectona grandis can be grown on less fertile land. This is even recommended by the government, where forest areas were set for planting with teak limited to places that are less fertile and steep. The growth of a plant can be influenced by environmental factors and genetic factors. The interaction between these two factors will determine the growth of a plant. The purpose of this study was to analyze the effectiveness of the Groove planting system (GPS) on the growth of teak ( Tectona grandis ) in limestone ex-mining areas. The method in this research was an experimental method that was carried out in the former limestone quarry of PT Semen Indonesia in 2020. The results showed that the growth of teak seen from the parameters of plant height, bar chart, leaf number, and leaf color increased. For example, leaf color with a conventional system has a scale of 3 with a GPS scale of 5. Conclusion The GPS method is very effective for the growth of teak ( Tectona grandis) because there is an increase in growth and color scale in terms of plant height, stem diameter, number of leaves, and leaf color parameters.